Pesticides, an urgent challenge to global environmental health and planetary boundaries - Vandenberg, Laura N.; Pierce, Elise J.; Arsenault, Rachel M. (Frontiers in Toxicology, 2025)
There is increasing evidence that pesticides act as endocrine disruptors, developmental toxicants, and reproductive toxicants. In this review, we describe several global challenges associated with pesticide production and use that put the health of human and wildlife populations at risk. These include: (1) the global production and use of pesticides is high, leading to increasing rates of release into the environment; (2) exposures to non-target species (including humans) are well documented, and pesticides often have adverse effects on these species; (3) pesticides, and especially those that are persistent organic pollutants, do not stay where they are used, contributing to ecosystem pollution far from their intended areas of application; (4) climate change can exacerbate the use of pesticides; and (5) social determinants of health (race/ethnicity, sex, and occupation) influence pesticide exposures and the adverse effects associated with these exposures. In 2009, the concept of planetary boundaries was introduced as a framework to evaluate how human actions impact earth systems. The planetary boundaries were based on a shared understanding that human activities have significant and sometimes irreversible effects on key aspects of environmental health. When considering the global impact of pesticides, these products can disrupt several planetary boundaries including biogeochemical cycles, biosphere integrity (e.g., measures of biodiversity), and the availability of clean freshwater, but the greatest challenge posed by pesticides is the “novel entities” boundary (i.e., the introduction of synthetic chemicals and materials into the environment). The planetary boundaries framework makes clear that failure to act against the most concerning chemicals, including pesticides, ultimately puts the survival of human populations at risk.